Ecosystem Services and Poverty Alleviation Trade-offs and Governance - Schreckenberg, Kate; Poudyal, Mahesh; Mace, Georgina (Routledge Studies in Ecosystem Services, 2018)
Understanding how to sustain the services that ecosystems provide in support of human wellbeing is an active and growing research area. This book provides a state-of-the-art review of current thinking on the links between ecosystem services and poverty alleviation. In part it showcases the key findings of the Ecosystem Services for Poverty Alleviation (ESPA) programme, which has funded over 120 research projects in more than 50 countries since 2010. ESPA's goal is to ensure that ecosystems are being sustainably managed in a way that contributes to poverty alleviation as well as to inclusive and sustainable growth. As governments across the world map how they will achieve the 17 ambitious Sustainable Development Goals, most of which have poverty alleviation, wellbeing and sustainable environmental management at their heart, ESPA's findings have never been more timely and relevant. The book synthesises the headline messages and compelling evidence to address the questions at the heart of ecosystems and wellbeing research. The authors, all leading specialists, address the evolving framings and contexts for the work, review the impacts of ongoing drivers of change, present new ways to achieve sustainable wellbeing, equity, diversity, and resilience, and evaluate the potential contributions from conservation projects, payment schemes, and novel governance approaches across scales from local to national and international. The cross-cutting, thematic chapters challenge conventional wisdom in some areas, and validate new methods and approaches for sustainable development in others. The book will provide a rich and important reference source for advanced students, researchers and policy-makers in ecology, environmental studies, ecological economics and sustainable development.